Laïcité scolaire et justice locale en France métropolitaine : hybridation des conceptions de la laïcité dans les pratiques enseignantes - Charlène Ménard (Cahiers de la Recherche sur l'Education et les Savoirs)
Universalism is presented, in the prescriptions for public school, as the keystone of the system of republican values, of which secularism is a part. This republican universalism is however questioned both by the current political issues of recognition and inclusion of ethnic and religious cultural diversity, but also by the concrete reality of the work of teachers. From interviews and ethnographic observations conducted in three different public secondary schools for two years, this article presents an analysis of teaching practice in situations of debate, tension, negotiation about the principle of secularism. How is secularism realized on a daily basis, in the interactions within public secondary schools? Based on a comparison of teaching practices between different public secondary schools (wealthy, socially mixed and disadvantaged), we will see that teaching strategies of adaptation and contextualization of the principle of secularism lead to a local interpretation of school justice, negotiated in situation with reference to different principles of justice, without losing sight of republican universalism.